Interspecific comparisons of the size of neural song control regions and song complexity in duetting birds: evolutionary implications - EA Brenowitz; Arthur P. Arnold (1986)
Previous studies have demonstrated a correlation between song repertoire size and volume of song control regions (SCRs) in the brains of songbirds. In the present study we demonstrate that 2 congeneric species of tropical duetting wrens, the rufous-and-white wren (Thryothorus rufalbus) and the bay wren (T. nigricapillus), share the same relationship between SCR volume and vocal complexity. In each species, females sing in elaborate duets with males. Males of these species have similar song repertoire sizes; there is no significant difference between heterospecific males in the volumes of SCRs. Female rufous-and-white wrens have less than half as large a song repertoire as female bay wrens, and all of their SCRs measured are significantly smaller than those of bay wren females. This interspecific equivalence of the relationship between SCR volume and repertoire size suggests that the neural system regulating vocal behavior in songbirds is evolutionarily conservative in the manner in which it encodes song complexity.